Cosmopolitanism and its discontents rethinking politics in the age of Brexit and Trump - Ward, Lee (Political theory for today., 2020)
This volume examines the cosmopolitanism ideal from ancient to contemporary times. It grapples with the question: Is there still relevance today for the idea of the "citizen of the world" that transcends national borders in the aftermath of the Brexit Referendum result and election of Donald Trump in 2016?